Pengaruh Pendapatan, Keadaan Tempat Tinggal, dan Akses Pendidikan Terhadap Kesejahteraan Masyarakat Kecamatan Woyla Barat dengan Adanya PT. Agro Sinergi Nusantara - Tomi; Bahri, Idal; Mawardi; Yuliana; Adami, Yulfrita (PENG: Jurnal Ekonomi dan Manajemen, 2025)
The purpose of this study was to determine whether there was an influence of income, living conditions, and access to education on the welfare of the people of Woyla Barat District with the presence of PT. Agro Sinergi Nusantara. The method used was field research with a sample of 69 people carried out at PT Agro Sinergi Nusantara in Lueng Gayo Village, Teunom District, Aceh Jaya. Data were collected using observation, interview, and documentation techniques in the form of primary data and secondary data using observation guide sheets and interview guide sheets. Data were analyzed partially (t-test) and simultaneously (f-test). The results of the study were: 1) there was a partial influence of income on welfare with a value obtained of 0.00 <0.05; 2) there was a partial influence of living conditions on welfare with a value obtained of 0.00 <0.05; 3) there was a partial influence of access to education on welfare with a value obtained of 0.00 <0.05; 4) there is a simultaneous influence of income, living conditions, and access to education on the welfare of the Woyla Barat District Community with the presence of PT ASN with the value obtained being 0.03 <0.05.